Strategi Pemasaran Kerajinan Topeng Ganongan untuk Melestarikan Budaya Lokal - Adelia Arda Fitrarizqiany; Arik Dwijayanto (Institut Agama Islam Sunan Giri Ponorogo, 2025)
Ganongan crafts, which are one of the traditional cultural icons of Ponorogo, play an important role in maintaining and preserving local cultural heritage. However, technological developments and changes in consumer preferences threaten the sustainability of this craft. This article aims to explore various marketing strategies that can be used to maintain and develop ganongan crafts, so that they can continue to exist amidst modern product competition. This research was carried out using a qualitative descriptive method, using a case study approach on several craftsmen in Dukuh Mirah, Nambang Rejo village, Sukorejo, Ponorogo. This research found that the success of preserving Ganongan crafts was greatly influenced by the craftsmen's ability to adopt innovative and adaptive marketing strategies. Several strategies that have proven effective include strengthening brand identity through distinctive cultural stories, using social media to increase public awareness, and collaborating with various parties such as the government, the arts community and academics to expand marketing networks. Apart from that, product diversification by combining traditional and contemporary elements is also key in attracting the interest of the younger generation.